Materials for medical devices - Narayan, Roger (ASM International, 2012)
This volume considers the most common materials used in medical devices. State-of-the-art reference information is given for implant materials including stainless steels, cobalt-base alloys, titanium, shape memory alloys, noble metals, ceramics, and polymers. Examples of materials- and mechanical-based failures of medical devices provide lessons learned in the failure analysis section. Biotribology and implant wear are covered extensively, including clinical wear and biological aspects of implant wear. A detailed look at corrosion includes its effects, corrosion products, mechanically assisted corrosion and corrosion fatigue. Biocompatibility is also discussed at length including biocompatibility of ceramics and polymers. Engineers with little exposure to medical and biomedical engineering will find this book particularly useful. It will help engineers and designers at all levels understand how materials react inside the body. Volume 23 is a replacement for the Handbook of Materials for Medical Devices edited by J.R. Davis (ASM, 2003). The new volume features brand-new content that greatly expands the scope and depth of coverage, including a more in-depth discussion of materials and focus on applications.
Keywords: Biomedical materials -- Handbooks, manuals, etc.; elektronické knihy; electronic books